2005
DOI: 10.1002/dc.20395
|View full text |Cite
|
Sign up to set email alerts
|

Subacute thyroiditis: Fine-needle aspiration cytology of 14 cases presenting with thyroid nodules

Abstract: Subacute thyroiditis (SAT) is usually diagnosed clinically without the need for fine-needle aspiration. The cytologic literature on this condition is therefore rare. We report on 14 cases of SAT presenting with thyroid nodules. The majority of patients were women with a mean age of 46 yr. All had pain/tenderness in the thyroid area accompanied by fever or an elevated ESR. The salient cytologic features included cellular smears; multinucleated giant cells in 100% of cases, some ingesting colloid or neutrophils;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 20 publications
0
46
1
2
Order By: Relevance
“…The cytologic literature on SGT is relatively rare, but the cytologic features of SGT has been well described. 1,[4][5][6]10,21 One report summarized the key cytologic features of SGT with performing Giemsa staining. 10 and after that, another report has been published that used Papanicolou stain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytologic literature on SGT is relatively rare, but the cytologic features of SGT has been well described. 1,[4][5][6]10,21 One report summarized the key cytologic features of SGT with performing Giemsa staining. 10 and after that, another report has been published that used Papanicolou stain.…”
Section: Discussionmentioning
confidence: 99%
“…10 and after that, another report has been published that used Papanicolou stain. 21 The aspirate of SGT usually dis- Our study was performed with Papanicolou stain and we were able to compare the reported cytologic features. 10,21 with those of our cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Si un certain nombre de critères cliniques peuvent orienter vers la malignité (tableau II), aucun n'est complètement spécifique [46][47][48][49]. Leur sensibilité est médiocre car seule une minorité de patients ayant un cancer présentent un ou plusieurs de ces critères.…”
Section: Quel Est Le Devenir Des Nodules Thyroïdiens ?unclassified
“…9 SGT is usually diagnosed clinically and therefore the cytological literature on this condition is rare. 3 SGT requires no specific treatment but there are other thyroid conditions which present with similar clinical manifestations that must be ruled out like acute thyroiditis and Grave's disea se, both of which require different therapeutic modalities. This diagnostic task is solved by means of fine-needle aspiration (FNA).…”
mentioning
confidence: 99%